New records of host plants of Raoiella indica Hirst in Colombia - León Martínez, Guillermo A. (2021)
Introduction. The red palm mite Raoiella indica Hirst (Acari: Tenuipalpidae) is recognized as a quarantine pest on coconut palm leaves, reported since 2004 in the American continent. In Colombia its presence was recorded in 2010 and it’s spread along the Atlantic coast has been rapid. In 2013 it was reported in the departments of Atlántico, Bolívar, Córdoba, Guajira, Magdalena, Norte de Santander, and Sucre, in coconut (Cocos nucifera), banana (Musa acuminata), heliconias, and plantain (Musa paradisiaca) plants. Objective. To know new host plants and the dispersal of the mite R. indica in three departments of Colombia. Materials and methods. During the years 2019 to 2020, in the Colombian departments of Meta (municipalities of Villavicencio, Guamal, San Carlos de Guaroa, and Granada), Casanare (municipality of Yopal) and Tolima (municipality of Guamo), plants of the families Arecaceae, Musaceae and Heliconiaceae, which could be hosts of the mite R. indica, were checked. Results. Of the twenty plant taxa sampled, sixteen were found to be hosts of R. indica and one of them was a new host. The presence of R. indica was recorded for the first time in the three departments, mainly on coconut palms and several alternate host plants including palms, mosses and Heliconia psittacorum. Conclusions. The red mite R. indica was reported officially for the first time in the Colombian departments of Meta, Casanare, and Tolima, and the seje palm, Oenocarpus bataua Burret, is reported as a new host plant species for R. indica in Colombia.